Funções absolutamente minimizantes - Amaral, Marcelo Dario dos Santos (2013)
The objective of this dissertation is to give an exposition of the theory of absolutely minimizing Lipschitz extensions, based on the work of Gunnar Aronsson, Michael G. Crandall and Petri Juutinen in [1], showing various details in a form accessible to readers without any prior knowledge of the subject. In particular, we retrace the improved results on the existence through arguments that are simpler than those that can be found in literature. We present a proof of the known uniqueness result, which is not based on the theory of viscosity solutions. In our approach we will show that the absolutely minimizing functions are the functions that satisfy a geometric condition which we will call to enjoy comparison with cones. This elementary geometric device renders the theory versatile and transparent. Here we will nd a priori continuity estimates, Harnack inequality, Perron's method for proving existence results, uniqueness and regularity questions, and some basic tools of viscosity solution theory. We believe that our presentation provides a uni ed sum-mary of the existing theory as well as some results of interest to experts and researchers and, at the same time, a source which can be used for introducing students to some signi cant analytical tools.